Analysis of Measurement Uncertainty in the Calibration of Digital Scales in the Downstream CPO (Crude Palm Oil) Production Unit - Bintang Tua Sitohang; Solly Aryza; Beni Satria (Sean Institute, 2025)
Calibration of measuring instruments is an important aspect in ensuring the accu-racy and reliability of industrial production systems, including in the palm oil derivatives (CPO) processing sector. Digital scales play a crucial role in the weighing process of raw materials, semi-finished products, and final products. However, each calibration process is inseparable from measurement uncertainty that can affect the quality of production results. Where this study aims to analyze the level of measurement uncertainty in the calibration process of digital scales used in CPO derivative production units. The research method is carried out by collecting scale reading data with standard loading, calculating type A (statistical) and type B (non-statistical) uncertainties, as well as calculating com-bined uncertainty and expanded uncertainty in accordance with ISO GUM (Guide to the Expression of Uncertainty in Measurement). Thus, the results of the analysis show that the greatest uncertainty comes from the variation in readings (repeatability) and the tol-erance of the standard weights used. The combined uncertainty value obtained is within the range that meets the industrial calibration tolerance limit, but there are recommenda-tions for improving environmental control procedures during calibration to minimize fur-ther deviations.